Numerical study of a symmetric single-sided vibro-impact nonlinear energy sink for rapid response reduction of a cantilever beam - Li, Wenke; Wierschem, Nicholas E.; Li, Xinhui; Yang, Tiejun; Brennan, Michael J. [UNESP] (Springer Nature, 2020)
This paper concerns an investigation into the control of the transient vibration of an Euler–Bernoulli beam using a symmetric single-sided vibro-impact nonlinear energy sink (SSSVI NES). The non-dimensional system of equations is derived by using the Galerkin method. Consideration and theoretical analysis of the impact dynamics of the device is carried out by introducing the impact modes. This analysis shows that the proposed SSSVI NES has increased complexity in its modes of energy dissipation compared with the single-sided vibro-impact NES (SSVI NES). Simulations are conducted with a wide variety of impulse loads to determine the optimum parameters of the SSSVI NES. The beam vibration suppression performance of the optimized SSSVI NES is then compared with both the SSVI NES and the case in which the NES is locked. When these devices have the same total mass, the SSSVI NES has superior vibration suppression performance, especially when the damping in the control device is light. The vibration suppression performance of the SSSVI NES is investigated when its location along the beam is varied. The effect of the clearance between the NES masses and the impact surface on the vibration suppression performance of the SSSVI NES is also investigated, as well as the device’s damping and the coefficient of restitution. Finally, the efficacy of the SSSVI NES device for seismic loads is investigated. The numerical results of this analysis show that the optimized SSSVI NES can effectively reduce the energy in the system and suppress the maximum bending moment and shear stress of the host cantilever beam.
Keywords: Cantilever beam; Nonlinear energy sink; Passive control; Vibro-impact